2x-5(x-4)=-5+4x-3

Simple and best practice solution for 2x-5(x-4)=-5+4x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-5(x-4)=-5+4x-3 equation:


Simplifying
2x + -5(x + -4) = -5 + 4x + -3

Reorder the terms:
2x + -5(-4 + x) = -5 + 4x + -3
2x + (-4 * -5 + x * -5) = -5 + 4x + -3
2x + (20 + -5x) = -5 + 4x + -3

Reorder the terms:
20 + 2x + -5x = -5 + 4x + -3

Combine like terms: 2x + -5x = -3x
20 + -3x = -5 + 4x + -3

Reorder the terms:
20 + -3x = -5 + -3 + 4x

Combine like terms: -5 + -3 = -8
20 + -3x = -8 + 4x

Solving
20 + -3x = -8 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
20 + -3x + -4x = -8 + 4x + -4x

Combine like terms: -3x + -4x = -7x
20 + -7x = -8 + 4x + -4x

Combine like terms: 4x + -4x = 0
20 + -7x = -8 + 0
20 + -7x = -8

Add '-20' to each side of the equation.
20 + -20 + -7x = -8 + -20

Combine like terms: 20 + -20 = 0
0 + -7x = -8 + -20
-7x = -8 + -20

Combine like terms: -8 + -20 = -28
-7x = -28

Divide each side by '-7'.
x = 4

Simplifying
x = 4

See similar equations:

| (x^2+5x-24)=(-x^2-4x+9) | | 9z^2+18z-48=0 | | 2797,04=(x*2140)/(3158,50*4) | | 4(t-4)+8t=6(2t+2)-8 | | 9z^2+18x-48=0 | | 23=5x-7x-1 | | 75.0=60+0.05t | | 6x^2+3=x | | 7-3(2x-1)=2x+2 | | 4(2x-1)=2x+26 | | 75.0=60+0.05 | | (4x-1)=(x+8) | | X^2=14+16x | | 5b+3-7b+8=1 | | -12+12x=9x+30 | | 3x-70= | | (2-x)=(8-x) | | b^2=5 | | 4(m-3)=16 | | -145+4x=-5+53 | | (3x+2y)(5x-3y)=0 | | 7+2m-4=7m-7-4m | | (a+2)=(3a+9) | | -25+2x=32-x | | .07x+84532=x | | -94+x=81-6x | | (3x-1)=(5x-2) | | 136=Y(X*4-7) | | 4y=4x+2 | | 3(5x-4)-(3x+2)=16 | | 9x=5x+56 | | 4(t-2)+6t=5(2t+2)-9 |

Equations solver categories